Advertising and Entry Deterrence: An Exploratory Model - Schmalensee, Richard (Journal of Political Economy, 1983)
In this model, the effects of advertising are infinitely durable, fixed (and sunk) costs give rise to economies of scale, post-entry behavior is noncooperative, and pre-entry expectations are rational. Despite the obvious resemblance to work on the use of investment in production capacity to deter entry, here the incumbent monopolist never finds it optimal to advertise more if entry is possible than if it is not. This result and other features of this model indicate the dangers of analyzing advertising with analogies to other sorts of investments. The results make clear the need for more theoretical work on advertising and entry deterrence.